Relationship between obesity and infertility among women with polycystic ovarian syndrome treated at the national population and family development board (NPFDB) Malaysia - Hasnoorina Husin; Mohd Azizuddin Mohd Yussof; Asmah Hamid; Ismarulyusda Ishak; Siti Balkis Budin (Universiti Kebangsaan Malaysia, 2023)
Polycystic ovarian syndrome (PCOS) is a metabolic dysfunction and is closely related to infertility in women. Obesity has an impact on the clinical manifestations of PCOS. This study was designed to determine the relationship between obesity and infertility among women with PCOS treated at the National Population and Family Development Board (NPFDB) Malaysia. This is a cross-sectional study with a simple random sampling technique involving infertile women attending NPFDB Subfertility Clinic, Kuala Lumpur, Malaysia, from January 2018 to December 2019. Clinical and menstrual history were recorded, and subjects underwent physical examination by a medical doctor. Subjects were diagnosed with PCOS based on Rotterdam criteria, and blood was taken for reproductive hormone, blood glucose, cholesterol, and triglyceride determination. A total of 179 infertile women completed the study, and 84 (47%) were diagnosed with PCOS. Results showed a significant increase in follicle-stimulating hormone (FSH) levels along with a significant reduction in progesterone level (p<0.05) in PCOS women compared to non-PCOS women. A total of 44% of PCOS women were found to be obese, and they exhibited significantly higher blood pressure and triglyceride level but lower high-density lipoprotein (HDL) level (p<0.05) Chi-square (χ2) showed PCOS women who are obese are more likely to experience ovulatory dysfunction, as evidenced by oligo- and amenorrhea, compared to non-obese women with PCOS. In addition, they were also presented with significantly higher testosterone levels (p<0.05) and reduced progesterone levels compared to non-obese PCOS women. This study showed that PCOS women with obesity had more prominent ovulatory dysfunction and reproductive hormonal imbalance than non-obese PCOS women. These findings suggest that PCOS women with obesity are more prone to develop infertility.